Efektivitas Penggunaan E-Modul Sistem Koloid Berbasis Inkuiri Terbimbing Terintegrasi Laboratorium Virtual Terhadap Hasil Belajar Peserta Didik Kelas XI SMAS Nurul ‘Ilmi - Siti Rahma Hasibuan; Andromeda (Dinasti Research, 2021)
This research is a continuation of the research on developing a colloidal system e-module based on guided inquiry integrated virtual laboratory which has been tested for validity and practicality but has not been tested for effectiveness. The purpose of this study was to determine the effectiveness of using the e-module colloid system based on guided inquiry integrated virtual laboratory on the learning outcomes of class XI students at SMAS Nurul 'Ilmi. This type of research is quasi-experimental research using the One-Group-Pretest-Posttest design. The results of the t-test at a significant level of 0.05 are count (2.82) > table (1.68). The N-Gain value in the subject class is 0.54. The results showed that the use of an e-module colloidal system based on a guided inquiry integrated virtual laboratory was effective in improving the learning outcomes of class XI SMAS Nurul 'Ilmi students.